Non-destructive testing method to quantify aging of materials by its apparent emissivity: Case of glass-based reflectors. (25th March 2017) - Riou, Olivier; Delaleux, Fabien; Guiheneuf, Vincent; Espargilliere, Harold; Logerais, Pierre-Olivier; Olives, Régis; Py, Xavier; Durastanti, Jean-Félix
Highlights: Aging of glass-based reflectors used in concentrated solar plants. Effects of damp heat protocol on infrared spectral emissivity of glass-based reflectors. Effects of damp heat protocol on normal LWIR apparent emissivity of glass-based reflectors. In-situ mapping of the aging of glass-based reflectors by utilizing apparent emissivity. Abstract: In this paper, the measurement capabilities of apparent emissivity are tested by means of a generic LWIR system to quantify the aging of materials. A theoretical frame permitted to elaborate abacuses and to correlate a scaling law to identify the relevant parameters, and to foretell performance in terms of absolute aging time interval resolution as well. The predictions are done for both indoor and outdoor situations. They are compared with measurements performed on glass-based mirrors of a heliostat of the solar furnace of Odeillo after having undergone a Damp Heat accelerated aging test. Apparent emissivity measurements implement an indoor home-made device which had already been characterized. The performances are in accordance with the predictions and allow to discriminate initial natural aging of glass mirror combined with accelerated aging with an interval resolution from 4 to 10 years keeping in mind that we are in quest of differentiating two mirror glasses or of quantifying the absolute aging of each mirror. Limitations of indoor measurements come mainly from the accuracy of Non-Uniformity Correction and from the internal drift compensation inherent to any IR system. Outdoor performances are foreseen to be as efficient by optimizing the contrast t app . - t env . . If we consider an uncertainty of emitting temperature of 0.25 °C and the one of apparent temperature of 0.1 °C, a standard outdoor thermography would enable to discriminate absolute aging produced by Damp Heat test with a 10 standard year resolution.